La modalidad de educación homeschooling o en casa para potenciar la escritura creativa en niños del tercer grado de la Escuela de Educación Básica Hermano Miguel del recinto Guamalán, parroquia San Pablo de Atenas, período lectivo 2020-2021. - Aroca Espín, Deysi Marilú (2021)
The present Educational Intervention plan called the homeschooling or home education modality to promote creative writing in children of the third grade of the EEB: “Hermano Miguel” of the Guamalán campus, San Pablo de Atenas parish, school period 2020-2021 constitutes a state of the art in a different and novel research modality within the recent homeschooling study modality in collusion with the specific area of Language and Literature in one of its essential components such as writing in the first years of schooling, in the same way it is summarized the design of a portfolio executed during the time of the pandemic with the application of the home schooling modality or with an emphasis on creative writing for its execution. These are ten sessions that meet the criteria: a) Total execution period between September and November 2020; b) Have an observation process to systematize it; and c) Be in direct relationship with the teaching of the national curriculum of the Ministry of Education during its execution. The analysis of these experiences and the lessons learned will show that the trend of this portfolio in this area of knowledge such as Language and Literature in general and the macro-skill of writing in particular is oriented towards teacher training in an innovative methodology and production of educational material that can be used to be applied in a special way at this time of phase one applied from the MinEduc. As such, the Educational Intervention Project is a psychopedagogical alternative that will improve the language skills of children in the third grade of the EEB. “Hermano Miguel” by executing the strategies designed in the short term with the help and collaboration of both the tutor and the parents themselves from home. The techniques applied to the boys and girls after they have been carried out can be visualized with the achievement in the development of the essential skills outlined for this purpose by the institutional authority, the teachers and the parents and / or representatives.